Arginine Increases Tolerance to Nitrogen Deficiency in Malus hupehensis via Alterations in Photosynthetic Capacity and Amino Acids Metabolism - Chen, Qi; Wang, Yanpeng; Zhang, Zhijun; Liu, Xiaomin; Li, Chao; Ma, Fengwang (Frontiers in Plant Science, 2022)
Arginine plays an important role in the nitrogen (N) cycle because it has the highest ratio of N to carbon among amino acids. In recent years, there has been increased research interest in improving the N utilization of plants, reducing the use of N fertilizer, and enhancing the tolerance of plants to N deficiency. Here, the function of arginine in the growth of apple plants (Malus hupehensis) under N deficiency was explored. The application of 100 μmol L-1 exogenous arginine was effective for alleviating N-deficiency stress. The net photosynthetic rate, maximal photochemical efficiency of photosystem II, and chlorophyll content were higher in treated plants than in control plants. Exogenous arginine promoted the absorption and utilization of N, phosphorus (P), and potassium (K) under low N stress. We also compared the metabolites of apple plants with and without arginine treatment. Arginine increased the content of amino acids and flavonoids under N deficiency, including delphinidin-3-O-arabinoside (4.3-fold), malvidin-3-O-arabinoside (1.9-fold), and kaempferol-3-O-rhamnosyl (1→2) glucoside increased (2.7-fold). Our results indicate that arginine improves the tolerance of apple to N deficiency by improving its photosynthetic capacity; the uptake, accumulation, and partitioning of N, P, and K; and the accumulation of metabolites (amino acids and flavonoids).